Thrombospondin‐1 Regulates Bone Homeostasis Through Effects on Bone Matrix Integrity and Nitric Oxide Signaling in Osteoclasts. (January 2015) - Amend, Sarah R; Uluckan, Ozge; Hurchla, Michelle; Leib, Daniel; Veis Novack, Deborah; Silva, Matthew; Frazier, William; Weilbaecher, Katherine N
Abstract Thrombospondin‐1 (TSP1), an endogenous antiangiogenic, is a widely expressed secreted ligand with roles in migration, adhesion, and proliferation and is a target for new therapeutics. While TSP1 is present in the bone matrix and several TSP1 receptors play roles in bone biology, the role of TSP1 in bone remodeling has not been fully elucidated. Bone turnover is characterized by coordinated activity of bone‐forming osteoblasts (OB) and bone‐resorbing osteoclasts (OC). TSP1−/− mice had increased bone mass and increased cortical bone size and thickness compared to wild type (WT). However, despite increased size, TSP1−/− femurs showed less resistance to bending than expected, indicative of diminished bone quality and a bone material defect. Additionally, we found that TSP1 deficiency resulted in decreased OC activity in vivo and reduced OC differentiation. TSP1 was critical during early osteoclastogenesis, and TSP1 deficiency resulted in a substantial overexpression of inducible nitric oxide synthase (iNOS). Importantly, administration of a NOS inhibitor rescued the OC function defects of TSP1−/− mice in vivo. To investigate the role of bone‐derived TSP1 in osteoclastogenesis, we found that WT pre‐OCs had defective iNOS expression when cultured on TSP1−/− bone compared to WT bone, suggesting that TSP1 in bone plays a critical role in iNOS signaling during OC development. These data implicate a new role for TSP1 in bone homeostasis with roles in maintaining bone matrix integrity and regulating OC formation. It will be critical to monitor bone health of patients administered TSP1‐pathway directed therapeutics in clinical use and under development. © 2014 American Society for Bone and Mineral Research.